ANGKA KEJADIAN NYERI TENGGOROK PASCA OPERASI SETELAH PEMASANGAN LARYNGEAL MASK AIRWAY (LMA) PROSEAL (Uji Banding pada Pasien yang di Induksi dengan Propofol 2,5 mg/kgbb ditambahkan Atracurium 0,5 mg/kkbb dan Propofol 2,5 mg/kgbb saja) - , GUNAWAN, Dr. Bhirowo Yudo P, SpAn,K ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Sore throat is a complication which frequently happened in postoperative patients under general anesthesia with endotracheal intubation. Laryngeal Mask Anesthesia (LMA) becoming an alternative device in order to diminish postoperative sore throat incidency under general anesthesia. LMA is generally inserted without the administration of muscle relaxant, but LMA insertion would need anesthesia state which deep enough. Propofol has the benefit to press down the upper airway reflex and served as fine general anesthesia induction to facilitate LMA insertion. Incidence of sore throat still remains high in LMA application inducted with Propofol agent. Hopefully, Propofol induction followed by muscle relaxant administration would enhance propofolâs relaxation effect thus could reduce trauma accompanying LMA insertion. LMA application which inducted either with Propofol and muscle relaxant could be as sublime choice as an alternative way to reduce the incidence of post operative sore throat. This research purposed on comparing post operative Propofol induced sore throat after the LMA Proseal insertion with or without administration of muscle relaxant. Double Blind Randomized Controlled Trial research design has been used with the study subjects of 120 male and female patients, 18-50 years, ASA I and II, whose underwent general anesthesia with LMA elective surgeries with the exclusion of head and neck surgeries. The study subjects have been divided into two groups with group A (60 patients) belonged to propofol and atracurium while group B (60 patients) belonged to propofol without atracurium. Sore throat incidence measurement has been done after patients were fully awakened and on 24 hours post operative. The research resulted on there were significant differences (p<0.05) in both studied groups toward sore throat after the patient fully-awake and 24 hours after the operative. After the patient fully-awake on Group A, there were 3 patients (5,1%) who experienced sore throat, whilst for Group B there were 10 patients (18,2%). There were 4 patients (6,7%) in group B who experienced sore throat on 24 hours post operative, but none in group A. LMA benificial comprising easier and faster insertion, so the sore throat incidence could deductible. Conclusion: there was lower incidence of sore throat after the inserstion of Porseal LMA in the propofol induction with muscle relaxant than that in the propofol induction without muscle relaxant after fully awake and 24 hours post operative.